2017
DOI: 10.1166/jctn.2017.6133
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Practice of a College English Teaching Platform Based on Artificial Intelligence

Abstract: College English is one of the basic core courses for all college students in China. The course involves many difficult concepts and grammatical structures, so it is difficult to most of the students. The starting point in any teaching program is to determine whether teaching is needed to specify what that teaching should accomplish. So the students’ need is of vital importance to the success of college English teaching. Traditional college English teaching does not take into account students’ individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Scientific data analysis and screening of evaluation indexes can ensure the data independence between evaluation indexes, so it is necessary to analyze the data correlation of the evaluation indexes set above. The correlation coefficient indicates the degree of closeness between random variables, and the correlation coefficient equation can be taken to judge the degree of correlation and mutual influence between indexes, as shown in equation (1).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific data analysis and screening of evaluation indexes can ensure the data independence between evaluation indexes, so it is necessary to analyze the data correlation of the evaluation indexes set above. The correlation coefficient indicates the degree of closeness between random variables, and the correlation coefficient equation can be taken to judge the degree of correlation and mutual influence between indexes, as shown in equation (1).…”
Section: Data Processingmentioning
confidence: 99%
“…The popularization of these technologies has realized the integration and sharing of teaching resources and promoted the communication between teachers and students. Moreover, it has made up for the deficiency of traditional classroom teaching, and improved the teaching quality of teachers and enhanced the learning interest of students, thus network experimental teaching platform has attracted more attention from universities [1].…”
Section: Introductionmentioning
confidence: 99%
“…In order to realise the stable control to the intelligent robot for college English teaching and construct the hierarchical sub-dimension space motion planning model of college English teaching intelligent robots, it is necessary to carry out the 7-degree of freedom (DOF) motion space planning of college English teaching intelligent robots, design the seven rotational DOF motion modes for college English teaching robots (Zou, 2017;Liu, 2017), and use the end pose estimator to perform attitude feature sensing acquisition and control constraint parameter analysis for English teaching robots.…”
Section: Motion Planning Model For English Teaching Robotsmentioning
confidence: 99%
“…Tsai (2016) found that by learning with Duolingo, the autonomous learning ability of the learners was increased, in terms of their self-regulation on learning on accessing time to learn, self-regulation on a regular basis, finding more materials to learn, evaluating one's learning, and adjusting learning strategies to have more effective learning. Zou (2017) established a college English teaching platform and used AI to analyze the needs and knowledge of students. This platform can adjust teaching progress and content through AI algorithms.…”
Section: Introductionmentioning
confidence: 99%